EP571 Sentinel node mapping in endometrial cancer: analysis of more than 200 cases of hysteroscopic injection of tracers. (1st November 2019) - Martinelli, F; Ditto, A; Bogani, G; Leone Roberti Maggiore, U; Chiappa, V; Evangelista, M; Liberale, V; Zanaboni, F; Raspagliesi, F
Abstract : Introduction/Background: To report on performance of hysteroscopic-injection of tracers (ICG and Tc99m) for sentinel-nodes (SLNs) mapping in endometrial cancer. Methodology: A single center retrospective evaluation of Prospectively collected data of Consecutive patients with endometrial cancer underwent SLNs mapping following hysteroscopic-peritumoral-injection of tracer. Evaluation of Detection Rate (DR) (overall-bilateral-aortic) and diagnostic-accuracy (A) among the entire cohort and comparison between tracers. Results: 231 procedures were performed. Mean age:60 years (28–84); mean BMI:27.3 Kg/m 2 (15–47). In 164 cases (70.9%) hysterectomy and mapping procedure were performed laparoscopically. The overall-DR of the technique was 94.1% (208/221) (10 cases excluded: 9 equipment failure; 1 vagal reaction). Bilateral pelvic mapping was found in 62.5% of cases (130/208) and was more frequent in the ICG group (73.8% vs 53.3%; p:0.001). In 47.6% of cases (99/208) SLNs mapped both to pelvic and aortic nodes, and in 5 cases (2.5%) only in the aortic area. In 8 patients (3.8%) SLNs were found in aberrant (parametrial/pre-sacral) areas. Mean number of detected SLNs was 3.7 (1–8). 26 patients (12.5%) had nodal involvement: 12- (46.2%) macrometastases; 6-(23.1%) micrometastases; 8-(30.7%) ITCs. In 6 cases (23.1%) only aortic nodes were positive; in 6 cases (23.1%) both pelvic and aortic nodes and in 14 cases (53.8%) only pelvic area was involved. Three false-negative results were found, all in the Tc99m group. All had isolated aortic metastases. Overall-sensitivity was 88.5% (95% CI: 71.7–100) and overall-negative-predictive-value (NPV) was 98.4% (95% CI 91.8–100). No differences in terms of overall-DR, overall-sensitivity and overall-NPV were found between the two tracers. Conclusion: Hysteroscopic-injection of tracer for SLNs mapping in endometrial cancer is as accurate as cervical injection with a higher DR in the aortic area. ICG improves bilateral DR. Disclosure: Nothing to disclose.